Researching the Socio-Political Dimensions of Mathematics Education
XIV, 280 p.
Keywords: This book examines mathematics education research from socio-political perspectives. It is organized in dialogic units which examine issues such as the critique of existing research results based on the adoption of socio-political approaches; the implications of alternative theoretical tools in researching mathematics education; the tensions emerging while conducting research in highly conflictive environments; the researchers’ positioning with respect to research participants; and the adoption of socio-political methodological frameworks. As a whole, the book serves to illuminate what it means to say that power is a central constituent of mathematics education practices and research. This book will be of interest to researchers in mathematics education and general education as well as to graduate students taking courses on mathematics education research.